Webinar “Mengenal Lebih Dekat Kekerasan pada Anak” Berhasil Meningkatkan Pengetahuan Masyarakat mengenai Kekerasan pada Anak - Fathiyyatul Khaira; Rahmani Welan; Westi Permata Wati; Noverika Windasari; Rizkia Chairani Asri; Fory Fortuna; Dwi Sabtika Julia; Septi Mayang Sarry; Satya Wydya Yenny (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Incidents of child abuse increase every year, including cases in West Sumatra. Violence experienced by children can cause physical disorders, impairment in cognitive, emotional, and social development, and discrimination in the social environment. The government has set rules regarding the protection of children against violence. Still, not all people know the forms of child abuse, their impact on children, and how to report child abuse cases. Therefore, we held a webinar,